AUTOMATION SYSTEM OF THE CONTINUOUS CASTING LINE CONTROL - V. A. Harkov; Ju. V. Sachenko (Литьë и металлургия)
The peculiarities of automation of the continuous horizontal casting line are examined in the article. The variants of application of different cutoff mechanisms are analyzed, the description of automatic contour band cutoff unit, working in combination with continuous casting line, is given.